2017
DOI: 10.3949/ccjm.84a.15141
|View full text |Cite
|
Sign up to set email alerts
|

Chronic constipation: Update on management

Abstract: Managing chronic constipation involves identifying and treating secondary causes, instituting lifestyle changes, prescribing pharmacologic and nonpharmacologic therapies, and, occasionally, referring for surgery. Several new drugs have been approved, and others are in the pipeline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 83 publications
0
31
0
Order By: Relevance
“…The benefits of stool softeners such as docusate sodium are unclear. Bulk‐forming, fiber‐based laxatives are generally not recommended for slow‐transit constipation such as that caused by anticholinergic effects.…”
Section: Specific Adverse Effectsmentioning
confidence: 99%
“…The benefits of stool softeners such as docusate sodium are unclear. Bulk‐forming, fiber‐based laxatives are generally not recommended for slow‐transit constipation such as that caused by anticholinergic effects.…”
Section: Specific Adverse Effectsmentioning
confidence: 99%
“…Excessive tension of the pubic-rectal muscle, by reducing the anorectal angle, may also result in hindered defecation and increases the need for displacement using a stronger abdominal compressor [43]. Similarly, in the case of voiding, excessive PFM tension may functionally hinder its initiation, resulting in the necessity of using the abdominal pressure [44]. This condition also favors the occurrence of constipation and, consequently, may increase the risk of hemorrhoids [44].…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
“…Similarly, in the case of voiding, excessive PFM tension may functionally hinder its initiation, resulting in the necessity of using the abdominal pressure [44]. This condition also favors the occurrence of constipation and, consequently, may increase the risk of hemorrhoids [44]. Abuse of the abdominal press is also one of the factors increasing the risk of lowering within the pelvic organs [45].…”
Section: Role Of Pelvic Floor Muscle In Continencementioning
confidence: 99%
“…Differentiations in the composition of the intestinal microbiota have been confirmed when constipated patients and healthy controls have been evaluated in different studies and have shown that Lactobacillus may play an essential role in the pathogenesis of chronic constipation [83]. Lactobacillus species as probiotics could reduce the migrating myoelectric complex (MMC) period and speed up small intestinal transit.…”
Section: Management Of Chronic Constipationmentioning
confidence: 99%